2019
DOI: 10.1002/bdm.2121
|View full text |Cite
|
Sign up to set email alerts
|

The gap between medical and monetary choices under risk persists in decisions for others

Abstract: Decisions under risk in the medical domain have been found to systematically diverge from decisions in the monetary domain. When making choices between monetary options, people commonly rely on a decision strategy that trades off outcomes with their probabilities; when making choices between medical options, people tend to neglect probability information. In two experimental studies, we tested to what extent differences between medical and monetary decisions also emerge when the decision outcomes affect anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…EV theory usually assumes a complex computation process and predicts a longer decision time (Su et al, 2013 ). Therefore, the results suggest that individuals may use multiple strategies in risky choices and shift between these strategies as a function of task and strategic variability, which is consistent with previous studies (Venkatraman et al, 2009 ; Ashby et al, 2018 ; Popovic et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…EV theory usually assumes a complex computation process and predicts a longer decision time (Su et al, 2013 ). Therefore, the results suggest that individuals may use multiple strategies in risky choices and shift between these strategies as a function of task and strategic variability, which is consistent with previous studies (Venkatraman et al, 2009 ; Ashby et al, 2018 ; Popovic et al, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…Why might we see a cautious shift in medical but not financial decisions? Economic and medical decisions seem to elicit different decision processes, where the former is focused on probabilities and the latter on outcomes (Pachur et al, 2014; Popovic et al, 2019). Moreover, increased risk-taking for others in financial decisions and decreased risk-taking in medical decisions is the pattern that manifests itself in the field, which could have affected decision-makers in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The affect gap is defined as the systematic difference in decision outcomes between affect-rich and affect-poor formats (Pachur et al, 2014). The affect gap has been demonstrated for decisions that affect the self and decisions for others (Popovic et al, 2019). Decision quality appears to be higher in affect-poor relative to affect-rich formats.…”
Section: Affect Gap and Decision Makingmentioning
confidence: 99%
“…In experimental designs that use financial outcomes for affect-rich and affect-poor formats such as the CCT, there is no consistent evidence of age differences in risk taking in affect-poor versus affect-rich decision formats, although older adults appear to be less sensitive to fluctuations in basic task parameters Weller et al, 2019). A recent study in younger adults demonstrated that the affect gap persists in decisions for others (Popovic et al, 2019). Further research is needed on the role of affect and decision making for self versus other in younger and older adults, using formats that are directly comparable.…”
Section: Affect Gap and Decision Makingmentioning
confidence: 99%